Risk Factors for Incidental Gallbladder Cancer Found During Cholecystectomy for Cholelithiasis: A Case–Control Study - Christina Liava; Patrick Starlinger; Patrick S. Kamath; Moira B. Hilscher (Gastro Hep Advances)
Background and Aims: Gallbladder cancer (GBC) is a rare type of cancer with a high rate of cancer-related mortality because it is usually diagnosed at an advanced stage; however, it may also be incidentally detected postcholecystectomy for cholelithiasis. We aimed to identify risk factors for GBC incidentally found during cholecystectomy for cholelithiasis. Methods: We performed a case–control study including patients with histologically confirmed GBC incidentally found during cholecystectomy for cholelithiasis and controls who underwent cholecystectomy for cholelithiasis. Patient and control data were collected retrospectively using the electronic patient database. Risk factors were identified using logistic regression analysis. Results: In total, 76 GBC patients and 1065 controls were included in the study. Among GBC patients, 65.8% presented acutely, 30.3% had chronic biliary symptoms, 0.3% were asymptomatic, and 43.4% had known cholelithiasis before symptoms. On multivariate analysis, when compared with controls, GBC was significantly associated with female gender (80.3% vs 56.7% controls, P < .001), age ≥ 68 years (86.8% vs 48.4%, P < .001), gallstone size ≥1.70 cm (73.2% vs 28.2% controls, P < .001), ascending cholangitis (12.5% vs 4.1%, P < .001), anemia prior to cholecystectomy (33.3% vs 13.9%, P < .001), and duration of cholelithiasis ≥5 years (31.6% vs 10.2%, P = .011). These factors were included in a predictive model that was validated in internal and independent datasets with a sensitivity of 87%, specificity of 59%, and accuracy of 73%. Conclusion: In this case–control study, 5 independent risk factors were identified for early detection of asymptomatic individuals with cholelithiasis at high risk of harboring GBC that might benefit from cholecystectomy. High clinical suspicion for GBC improves the management of patients with cholelithiasis through advanced imaging work-up and appropriate surgical approach, avoiding reoperations.